Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/jbc.m113.475319
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feedback Regulation of Human Inducible Nitric-oxide Synthase Expression by Ras Protein S-Nitrosylation

Abstract: Background: Feedback regulatory processes controlling iNOS expression are incompletely defined. Results: Induction of iNOS expression was attenuated by 1) inhibition of iNOS activity, 2) prevention of Ras S-nitrosylation, and 3) inhibition of PI3K and mTOR activity. Conclusion: iNOS-derived NO amplifies iNOS expression through S-nitrosylation of Ras and activation of PI3K and mTOR. Significance: We have defined a previously unrecognized positive feedback pathway that amplifies human iNOS expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…The expressions of all NOS isoforms were enhanced by SNP and reduced by l-NAME suggesting thereby that NO may regulate NOS expression in ovary through feedback mechanism. This positive feedback control of eNOS, iNOS and nNOS expressions in fish may be similar to the recent report by Lee and Choy (2013) who have shown that NO augments iNOS expression in human lung epithelial cell line (A549) through S-nitrosylation of Ras and activation of PI3K and mTOR. Yuhanna and coworkers (1999) have also demonstrated the positive feedback control mechanism of eNOS expression by NO in human lung.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The expressions of all NOS isoforms were enhanced by SNP and reduced by l-NAME suggesting thereby that NO may regulate NOS expression in ovary through feedback mechanism. This positive feedback control of eNOS, iNOS and nNOS expressions in fish may be similar to the recent report by Lee and Choy (2013) who have shown that NO augments iNOS expression in human lung epithelial cell line (A549) through S-nitrosylation of Ras and activation of PI3K and mTOR. Yuhanna and coworkers (1999) have also demonstrated the positive feedback control mechanism of eNOS expression by NO in human lung.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, NO is also known to inhibit the expressions of eNOS (Grumbach et al 2005) and nNOS in rat forebrain (De Alba et al 1999). Though it is suggested that NO may use varieties of mode and mechanism to exert these feedback control on NOS expressions (Griscavage et al 1993, De Alba et al 1999, Yuhanna et al 1999, Hinz et al 2000, Lee & Choy 2013, no study has been carried out so far to examine that how these feedback regulation of NOS expression by NO is terminated. The experimental design of the present study does not permit us to comment on this aspect, however, considering the wide-ranging biological actions of NO in tissuespecific manner, it may be proposed that perhaps the redox status and concentration of NO of the target cells, bestowed with specific cellular machinery and molecular ambience, altogether may decide the type of feedback effect of NO on the NOS expressions and their termination.…”
Section: Discussionmentioning
confidence: 99%
“…3 A and C and SI Appendix, Fig. S11), presumably owing to alterations in positive feedback mechanisms on the transcriptional level (38). Effective inhibition of NO release was reflected by widely preserved neuronal morphology (Fig.…”
Section: Lps or Ifn-γ Alone Induces Reactive Phenotypes In Microglia mentioning
confidence: 99%
“…NO can act as a neurotransmitter or is used to nitrosylate cysteine (S-nitrosylation) or tyrosine (Nytril-tyrosine) residues in a plethora of signalling molecules, thus changing their activity (Mehta et al, 2008;Lee & Choy, 2013;Suárez et al, 2009). We analysed the S-nitrosylation levels of proteins upon expression of Drp1-S637A, Drp1-K38A and GFP in PC12 cells, and as predicted, cell lysates expressing Drp1-S637A to increase mitochondrial fission exhibited an increase in S-nitrosylated proteins when compared with cell lysates expressing Drp1-K38A or GFP (Fig.…”
Section: Drp1 Activity Regulates Inos Levels In Dvcmentioning
confidence: 99%